Pengaruh Pemberian Ekstrak Buah Naga Putih (Hylocereus undatus)Terhadap Struktur Histologis Paru Mencit (Mus musculus) Yang Dipapar Asap Rokok - Nurul Wahda Aulia; endang listyaningsih s; yulia sari . (Nexus Biomedika, 2013)
Background: White Dragon fruit contains substances like vitamin A, E, C and polyphenolic compound that can counteract free radical. Cigarette smoke is a type of oxidant compound that causes oxidative stress and lung damage. The purpose of this study was to determine the effect of White Dragon fruit extract on histological of the alveolar lung of mice exposed by cigarette smoke, and to find out whether the increase in dose enhanced the protective effect against histological of the alveolar lung exposed by cigarette smoke. Methods: This study was a laboratory experimental research with the post-test only control group design. The subjects used in this experiment was male Swiss Webster mice (Mus musculus), 2-3 months old and 20g of body weight. Sampling technique was incidental sampling. Twenty eight mice were divided into 4 groups, each group consisted of 7 mice. Negative control group / KK(-) was administered distilled water. Positive Control Group/ KK(+) was administered distilled water, then, 2 hours later was treated with cigarette smoke. Treatment group 1 (KP1) and 2 (KP2) were administered white dragon fruit extract with dose 70 mg/20 g and 140 mg/20 g, successively, then, 2 hours later were treated with cigarette smoke. These treatments were performed for 14 days. On the day 15, all lungs of subjects were prepared for histological study. Lung damage was assessed by looking at the destruction of the alveolar septum, pulmonary edema, and infiltration of inflammatory cells. Observation result were classified into normal category, moderate and serious. Then, the data were analyzed using the Kruskal-Wallis test and Mann Whitney test with ? = 0.05. Results: The Kruskal-Wallis test showed that at least one group had significantly greater effect than other groups with p = 0.004 (p <0.050). The Mann Whitney test showed significant difference between KK(-) KK(+), KK(-) - KK2, KK(+) - KK1 groups and no significant difference between KK(-) KK, KK(+) - KK2, KK1 KK2 groups. Conclusions: White Dragon fruit extract provided protective effect against mices lung histological damage from cigarette smoke. The increasing dose of White Dragon fruit extract did not enhance the protective effect of histological lung structure of the mice against cigarette smoke. Keywords:White Dragon fruit, cigarette smoke, histological damage of lung.